[Fishermen and Fish Along Husavik] - Streng, Evelyn Fiedler (1975)
Photograph of fishermen and fish along the Husavik harbor. A stack of grey fish lay on an orange tarp on a grey dock to the left. Piles of black net and white rope is visible past the fish. Two men, both wearing green shirts, stand along the dock and along a green boat at the center of the photograph. The gren boat has a small, white tower with Icelandic text written along it. The town is visible in the background consisting of white buildings with red and green roofs.